Communication about personal values of patients with advanced lung cancer in the hospital: results of a mixed-methods study - Villalobos Bollen, Matthias Americo; Ludwig, Jan Ole; König, Mara; Unsöld, Laura; Siegle, Anja; Thomas, Michael (Lung cancer, 2025)
Background - Guidelines recommend to discuss the treatment and care goals of patients with advanced cancer in alignment with their values and preferences, yet this approach is often not adequately implemented in hospitals. To explore the personal values of patients with metastatic lung cancer and how they communicate them to physicians, a mixed-methods study was conducted at a German University Lung Cancer Center. - Methods - The study included quantitative data from 66 patients with metastatic lung cancer using the Human Values Scale, a group comparison after propensity score matching with the German cohort from the 9th European Social Survey, semi-structured in-depth interviews (n = 17), qualitative content analysis, and integration of the data using side-by-side display. - Results - The quantitative analysis showed that patients prioritized the value dimensions of self-transcendence (universalism, benevolence; p = 0.02) and openness to change (self-direction, stimulation; p = 0.03), with a shift toward stronger self-direction in more advanced disease. In contrast, values related to conservation (conformity, tradition, security; p = 0.04) and self-enhancement (power, achievement; p = 0.02) were less important. Despite these stated preferences, qualitative data revealed that personal values and existential concerns were largely overlooked in clinical encounters. Patients often accepted physicians’ treatment recommendations without question, suggesting a gap in addressing their values and preferences. - Conclusions - Our findings highlight the need for physicians to take a proactive role in discussing patient values and empowering them in decision-making. These insights can inform the development of value assessment tools and interventions to improve shared decision-making and goal-concordant care.